2012 IEEE International Reliability Physics Symposium (IRPS) 2012
DOI: 10.1109/irps.2012.6241856
|View full text |Cite
|
Sign up to set email alerts
|

Geometry, kinetics, and short length effects of electromigration in Mn doped Cu interconnects at the 32nm technology node

Abstract: Mn doping in Cu seed has been used to improve EM performance at the 32nm technology node. This paper will show that on an optimized process with CuMn there were different degrees of EM enhancement for geometric variations including line width and electron flow direction. In addition, kinetics experiments on several geometries resulted in activation energies in the range of 0.95-1.33eV. Finally, the Blech threshold (jL)c=338mA/um was derived from the experimental data on various line lengths and current densiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…But more importantly, narrow Ru interconnected lines require a thinner barrier layer compared to copper interconnected lines. [301] Seong Jun Yoon et al demonstrated that maximizing the grain sizes in Ru interconnected lines can effectively lower the total line resistivity [302]. The total line resistivity has been successfully reduced by more than 30% by suppressing the grain boundary scattering effect.…”
Section: Metal Materials Interconnectmentioning
confidence: 99%
“…But more importantly, narrow Ru interconnected lines require a thinner barrier layer compared to copper interconnected lines. [301] Seong Jun Yoon et al demonstrated that maximizing the grain sizes in Ru interconnected lines can effectively lower the total line resistivity [302]. The total line resistivity has been successfully reduced by more than 30% by suppressing the grain boundary scattering effect.…”
Section: Metal Materials Interconnectmentioning
confidence: 99%
“…However, scaling can significantly reduce the electromigration (EM) lifetime for Cu interconnects, raising serious reliability concern for advanced technology nodes. Some improvements have been developed to improve EM and to extend the technology node by using CoWP metal cap [247,248] and Mn alloying [249][250][251].…”
Section: Metal Materials Interconnectmentioning
confidence: 99%
“…A self-forming barrier uses a Cu-X alloy-based seed layer to form the barrier layer by post metallization annealing. Among the tested alloying elements are V, Al, and Mn [249][250][251]271,272]. Mn-based self-formed barrier (SFB) is an attractive alternative technique from RC performance point of view.…”
Section: Metal Materials Interconnectmentioning
confidence: 99%
“…For example, alloying element Mn can enhance EM performance through forming a metallic-state Mn-rich Cu layer at the interface to stop copper diffusion [2]. The degrees of EM enhancement can also vary with line width and electron flow direction [3]. Different effects are induced by alloying elements in Cu interconnect.…”
Section: Introductionmentioning
confidence: 99%